ASSOCIATED FACTORS AND IMMEDIATE OUTCOME IN BIRTH ASPHYXIATED TERM NEONATES ADMITTED IN TERTIARY CARE HOSPITAL IN TRIBAL REGION OF INDIA-AN OBSERVATIONAL STUDY - PATIL, PUSHPARAJ NILKANTH; KHAN, ZUBAIR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective is to study the associated risk factors and outcomes of birth asphyxia (BA). Methods: The study involved 240 neonates of both genders who were admitted to the NICU of the Department of Pediatrics at NAMO MERI and SVBCH Hospital. Relevant information such as neonatal information, maternal information, and problems during pregnancy or labor noted and analyzed. Results: Among the cases and controls, the male-to-female ratio was 1.3:1 and 1.09:1, respectively. The incidence of meconium-stained liquor was higher in some cases, and these infants required longer resuscitation compared to controls (p<0.0001). Maternal risk factors such as hypertension, antepartum hemorrhage, and prolonged second stage of labor were significantly associated with BA (p<0.05). In addition, BA was significantly associated with hypoxic-ischemic encephalopathy (HIE), convulsions, and apnea (p<0.05). Top of FormBottom of FormThere was a significant correlation between the duration of resuscitation and the grade of HIE in asphyxiated babies (p<0.05). A severe form of HIE was developed in cases with a longer duration of resuscitation. The duration of resuscitation was longer in patients who were delivered in either a primary health center or home compared to a tertiary care hospital (p<0.05). Conclusion: Effective post-delivery resuscitation, additional basic steps, and training health workers and a skilled person at every birth can help reduce the occurrence of BA and its complications in resource-limited peripheral systems. This study highlights importance of maternal risk factor assessment, prompt resuscitation.